(untitled) (Indian Journal of Animal Production and Management, 2014)
The present study was carried out in Guntur district of Andhra Pradesh to know various husbandry practices followed by the Shepherds. The information was collected from 240 sheep farmers from three divisions of the district by pre tested questionnaire. It was observed that all the farmers in the area were rearing sheep extensively. Significantly more (95.00%) number of shepherds studied were providing housing to their sheep out of which 60.70% of the shepherds housed their sheep nearer to the dwelling house. Majority of the respondents (96.12%) had mud floor in the shed and 91.70% of the farmers sent their animals for grazing and the duration was about 8-10 h, while the grazing distance ranged from 2-4 km (67.90 %) to 4-6 km (32.10%). Sheep were mostly maintained on grazing without any extra feeding of concentrates. However, small number of sheep, maintained by farmers were fed little amount of concentrate. Flock mating was commonly followed and flushing was not at all practiced by the shepherds. June to August and January to March were found to be the two breeding seasons for the sheep in the area. All the shepherds studied were attending and cleaning the lambs after lambing. It might be concluded from the study that lower socioeconomic group rear the sheep for their livelihood with minimum inputs. Supplementary feeding with concentrates and dry fodder in required quantities might be practiced to obtain better growth and production performance during forage scarcity.